Quantifying the geodiversity of a study area in the Great Hungarian Plain - Őrsi, Anna (Journal of Environmental Geography, 2011)
Geodiversity is understood as the diversity of the abiotic nature. It expresses the variety of stones, minerals, fossils, places, landforms, processes, soils and elements of hydrology. As geodiversity assessment is a rather new research area, the number of publications concerning geodiversity is growing fast. In this paper we quantified the geodiversity of a study area located at the Danube-Tisza Interfluve in the Great Hungarian Plain using the method worked out by Hjort and Luoto (2010). We wanted to know how the diversity varies in space at low-land areas applying different indexes. Geodiversity was represented by three different indexes. Total geodiversity was calculated by summariz-ing the geologic features, the landforms and the elements of hydrology found in each unit. Then we grouped the landforms by the (exogenic) processes which formed them, and the number of these processes gave the value of the geomorphologic process diversity. Finally we calculat-ed the geodiversity index by Serrano-Canadas and Ruiz-Flano (2007). The absolutely homogenous units (totally waterlogged areas and the flat sand sheets) have the lowest geodiversity. It is higher at the border of the sandy, peaty and waterlogged areas. At this lowland area there is no relationship between the geodiversity and the relief. This is the first work applying this method in Hungary, so the results are yet not com-parable.